Alterations of brain metrics in fetuses of women with polycystic ovary syndrome : a retrospective study based on fetal magnetic resonance imaging - Zhongkun Bao; Qing Zhang; Manman Pan; Xi Xi; Yuanlin Wang; Fangfang Zhang; Fangfang Wang; Yu Zou; Fan Qu (BMC, 2021)
Abstract Background Maternal polycystic ovary syndrome (PCOS) has potential detrimental effects on the neurodevelopment of offspring. This study aimed to evaluate the brain metrics in fetuses of women with PCOS based on fetal magnetic resonance imaging (MRI). Methods This retrospective study included 60 pregnant women with PCOS (PCOS group) and 120 pregnant non-PCOS women (control group). Fetal MRI was performed followed an ultrasound and for numerous clinical indications including known or suspected fetal pathology, history of fetal abnormality in previous pregnancy or in a family member. Fetal brain biometry and apparent diffusion coefficient (ADC) value were analysed. Results After adjusting for potential confounders, fetuses in the PCOS group showed the following characteristics compared to fetuses in the control group: (1) smaller cerebral fronto-occipital diameter (FOD), vermian height (VH) and anteroposterior diameter of the pons (APDP) (evident before 32 weeks; P = 0.042, P = 0.002 and P = 0.016, respectively); (2) larger left and right biparietal index (evident before 32 weeks; P = 0.048 and P = 0.025, respectively); (3) smaller left lateral ventricle (LV) (evident after 32 weeks; P = 0.005); (4) larger anteroposterior diameter of the vermis (APDV) and hippocampal infolding angle (HIA) (evident after 32 weeks; P = 0.003 and P < 0.001, respectively); (5) higher ADC value in frontal white matter (FWM) and in basal ganglia (BG) (evident before and after 32 weeks; all P < 0.05). Conclusions There exist a different pattern of brain metrics in PCOS offspring in utero.